2017
DOI: 10.3892/etm.2017.4863
|View full text |Cite
|
Sign up to set email alerts
|

A crossover study of the combination therapy of metformin and exenatide or biphasic insulin aspart 30 in overweight or obese patients newly diagnosed with type 2 diabetes mellitus

Abstract: Abstract. The aim of the present study was to explore the effects of various combinations of exenatide, metformin (MET) and biphasic insulin aspart 30 (BIA30) on type 2 diabetes mellitus (T2DM). Two hundred overweight or obese patients newly diagnosed with T2DM were evenly randomized into two groups: A (twice daily for all: Phase I, 5 µg exenatide + 0.5 g MET for 4 weeks, then 10 µg exenatide + 0.5 g MET for 8 weeks; Phase II, 0.5 g MET for 12 weeks; Phase III, 0.3-0.4 U/kg/day BIA30 + 0.5 g MET for 12 weeks) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 35 publications
(36 reference statements)
0
10
0
Order By: Relevance
“…They comprised 6749 patients (inflammation evaluated in 6560, oxidative stress in 701 patients), included a median (IQR) study population of 60 (33‐122) participants, and had a median (IQR) follow‐up of 6 months (84‐182 days). Trials recruited from 11 individual countries and were multinational in four cases (14 from China, 30–33,37–39,41,44,47,48,56,58,65 seven from the United States, 36,52,53,59,61,63,68 three international studies, 46,64,66 three from Italy, 49,62,67 three from Japan, 45,55,57 two from Denmark, 50,69 two from Greece, 42,54 two Sweden, 34,35 one from France, 51 one from Germany, 60 one from India, 40 and one from Spain 43 ). Participants had a mean age of 53.1 years, 56.3% were women, the mean HbA1c was 55.6 (±8.89) mmol/mol, the mean BMI was 28.8 (±3.52) kg/m 2 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They comprised 6749 patients (inflammation evaluated in 6560, oxidative stress in 701 patients), included a median (IQR) study population of 60 (33‐122) participants, and had a median (IQR) follow‐up of 6 months (84‐182 days). Trials recruited from 11 individual countries and were multinational in four cases (14 from China, 30–33,37–39,41,44,47,48,56,58,65 seven from the United States, 36,52,53,59,61,63,68 three international studies, 46,64,66 three from Italy, 49,62,67 three from Japan, 45,55,57 two from Denmark, 50,69 two from Greece, 42,54 two Sweden, 34,35 one from France, 51 one from Germany, 60 one from India, 40 and one from Spain 43 ). Participants had a mean age of 53.1 years, 56.3% were women, the mean HbA1c was 55.6 (±8.89) mmol/mol, the mean BMI was 28.8 (±3.52) kg/m 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Participants had T2DM (39 trials) or prediabetes (three trials), and had a mean diabetes duration of 7.46 (±4.22) years (Table 1). In 16 studies (20.8% of total participants), both the active and control arms were also receiving concomitant metformin, 33,35,40,43,45,48,50–54,61–63,65,67 whereas the presence of concomitant medications was not clear in 11 studies (25.2% of total participants) 30,32,36,38,39,44,47,56–58,64 . In three studies (5.8% of total participants) >50% of participants received concomitant metformin and other diabetes medications 45,51,61 .…”
Section: Resultsmentioning
confidence: 99%
“…Jin and coworkers in 2020 demonstrated that liraglutide reversed HFD induced hyper-resistinemia in rats [ 73 ]. Quan et al in 2017 found that exenatide therapy significantly decreased resistin level in obese newly diagnosed diabetic patients [ 89 ]. Li et al in 2015 reported that liraglutide downregulated resistin peptide in patients with T2DM [ 90 ].…”
Section: Resistinmentioning
confidence: 99%
“…Included studies were published between 2008 and 2020. 8,9,[16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] The range of treatment duration was from 12 to 52 weeks. Only 1 study was cross-over, 19 and 19 out of the 20 included trials had a parallel design.…”
Section: Characteristics Of Clinical Trialsmentioning
confidence: 99%
“…8,9,[16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] The range of treatment duration was from 12 to 52 weeks. Only 1 study was cross-over, 19 and 19 out of the 20 included trials had a parallel design. Trials enrolled subjects with type 2 diabetes, 8,9,16-26,28,29,31 type 1 diabetes, 33 nonalcoholic steatohepatitis, 27 nonalcoholic fatty liver disease, 24,31 polycystic ovary syndrome 30,32 and hypertension.…”
Section: Characteristics Of Clinical Trialsmentioning
confidence: 99%